Respuesta :
Answer:
[tex]LM = MJ = 3[/tex]
[tex]JK = KL = \sqrt{17[/tex]
Step-by-step explanation:
Given
[tex]J = (4,5)[/tex]
[tex]K = (5,1)[/tex]
[tex]L = (1,2)[/tex]
[tex]M = (1,5)[/tex]
Required
Prove it's a kite
Start by calculating the length of the sides of the kite using:
[tex]d = \sqrt{(x_1 - x_2)^2 + (y_1 -y_2)^2}[/tex]
[tex]JK = \sqrt{(4 - 5)^2 + (5 -1)^2} = \sqrt{17}[/tex]
[tex]KL = \sqrt{(5 - 1)^2 + (1 -2)^2} = \sqrt{17}[/tex]
[tex]LM = \sqrt{(1 - 1)^2 + (2 -5)^2} = \sqrt{9} =3[/tex]
[tex]MJ = \sqrt{(1 - 4)^2 + (5 -5)^2} =\sqrt{9} = 3[/tex]
Hence:
[tex]LM = MJ = 3[/tex]
[tex]JK = KL = \sqrt{17[/tex]
proves that it is a kite
Answer:
B) LM = JM = 3 and JK = LK = [tex]\sqrt{17}[/tex]
Step-by-step explanation:
Edge 2021
Good Luck :)